Arkæologihistorie – Anmeldelser en bloc - Gjerløff, Anne Katrine (Kuml, 2002)
A History of Archaeology Reviews en bloc Taking the reviews of a number of publications on the history of archaeology from Gothenburg University as the starting point, new trends within the history of archaeology and the humanities in general are discussed. Importance is now attached to a contextual concept of the humanities and on a rehabilitation of the importance of the individual, especially in the works of Åsa Gillberg. With a Foucault-inspired approach, Ola W. Jensen is dealing with the connection between a Christian approach to history and the attitude to prehistory and the artifacts in the time until 1700. Anders Gustafsson, on the basis of an analysis of conprehensive publications on the history of archaeology, discusses the self-concept of archaeology and arrives at the conclusion that the history of archaeology is not history, but more exactly meta-archaeology. The article ends with the wish that the Danish history of archaeology will reach the high degree of publication and technical refining, which characterizes the Swedish publications. Anne Katrine Gjerlöff Institut for Historie Københavns Universitet Translated by Annette Lerche Trolle